Acceptability and validity of a home exercise diary used in home‐based pulmonary rehabilitation: A secondary analysis of a randomised controlled trial. (21st February 2018) - Lahham, Aroub; McDonald, Christine F.; Mahal, Ajay; Lee, Annemarie L.; Hill, Catherine J.; Burge, Angela T.; Cox, Narelle S.; Moore, Rosemary; Nicolson, Caroline; O'halloran, Paul; Gillies, Rebecca; Holland, Anne E.
Abstract: Introduction: Evaluating adherence to home‐based pulmonary rehabilitation (PR) could be challenging due to lack of direct supervision and the complex nature of the rehabilitation model. To measure adherence to home‐based PR in the HomeBase trial, participants were encouraged to work towards a goal of at least 30 min of whole‐body exercise on most days of the week and report their participation using a home exercise diary. Objective: This project aimed to evaluate the acceptability and validity of the home exercise diary. Methods: Diary return and completion rates assessed acceptability of the home exercise diary. Home participants underwent physical activity (PA) monitoring using the Sensewear armband during the final week of an 8‐week PR. The correlation between self‐documented and objective daily exercise minutes was calculated. Objective exercise minutes were defined as bouts of ≥10 min spent in ≥ moderate PA. Differences in self‐documented weekly exercise minutes between sufficiently active (≥7000 daily steps) and inactive participants were computed. Results: Diaries were returned by 92% of programme completers. Of those who returned diaries, 72% have completed exercise documentation. Fifteen programme completers underwent PA monitoring [mean age 69 (9) (SD) years, FEV1 55 (19) %predicted]. A moderate correlation was observed between self‐documented and objective mean daily exercise minutes ( r  = .59, P  = .02). Active participants [ n = 6, 10 253 (1521) daily steps] documented more exercise (111 min) during week eight compared with inactive participants [ n = 9, 2705 (1772) daily steps, P  = .002]. Conclusion: The self‐documented home exercise diary is an acceptable and valid method to reflect exercise participation during home‐based PR.